Meningkatkan Hasil Belajar IPA Menggunakan Model PBL, SAVI, dan Snowball Throwing - Oksi Vani Rulita; Susilawaty (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem is the low level of student activity and learning outcomes. Problems are caused by one-way learning, students do not understand the material, monotonous, boring learning, lack of cooperation, passivity during discussions, lack of active student involvement in the learning process. The aim of this research is to describe teacher activities in implementing science learning, describe student activities when participating in science learning, and analyze student learning outcomes in science learning. Efforts made to overcome the above problems are by applying a combination of the PBL, SAVI, and Snowball Throwing models. The subjects of this research were 22 grade 4 students. The research results showed that teacher activity reached the "Very Good" criterion, student activity also increased to reach the "Very Active" criterion, and student learning outcomes increased to 80% classical completion. Based on the results obtained, it can be concluded that there has been an increase in student activity and learning outcomes using a combination of PBL, SAVI and Snowball Throwing models.